2019
DOI: 10.1111/jpn.13206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary inclusion of cumin seed oil on the performance, egg quality, immune response and ovarian development in laying hens under high ambient temperature

Abstract: The objective of the present study was to find the effect of cumin seed oil (CSO, Cuminum cyminum L.) on the laying performance, ovarian follicular development and immune response in laying hens under high ambient temperature. A total of 162 Boven hens were randomly divided into three treatments and were fed, ad libitum, diets containing 0 (control), 250 or 500 g CSO per ton from 24 to 30 weeks of age. The experiment was done during summer season where the average temperate was 30 to 36°C. Feed intake and egg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 26 publications
4
23
0
Order By: Relevance
“…The evaluation of blood biochemical might be useful for the diagnosis of chicks pathologies and physiological status (Saleh, Kirrella, Dawood, & Ebeid, 2019). ALT and AST levels ranged respectively from 8.89 to 9.95 and 115.84 to 120.17, which were within acceptable ranges in chicken (Habibian et al, 2014).…”
Section: Discussionmentioning
confidence: 89%
“…The evaluation of blood biochemical might be useful for the diagnosis of chicks pathologies and physiological status (Saleh, Kirrella, Dawood, & Ebeid, 2019). ALT and AST levels ranged respectively from 8.89 to 9.95 and 115.84 to 120.17, which were within acceptable ranges in chicken (Habibian et al, 2014).…”
Section: Discussionmentioning
confidence: 89%
“…The obtained results also revealed improved ND titer in broilers fed OCM and/or BL, which indicates an improved immunity and, consequently, resistance against infectious diseases. Balanced diets supplemented with reasonable functional feed additives usually can keep high immunity status and resistance against infectious diseases in broilers [1,2]. Probiotics, on the other hand, are beneficial microorganisms that compete with the harmful bacteria in the animals' gut and provides the host high resistance against infectious diseases [43].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of increasing demand, limited supply, and a dramatic increase in the prices of feed ingredients, suitable alternative sources for poultry feed have recently been intensively studied [1,2]. Feed cost may account for more than 70% of the total production costs of broilers [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the levels of total amino acids in serum, liver, feather, and carcass can reflect the amino acids utilization (Kaczmarek et al 2014;Azzam et al 2015Azzam et al , 2017Dong et al 2016;Morales et al 2017;Wecke et al 2018;Middendorf et al 2019). In addition, amino acids concentrations in carcass could be used to determine amino acid requirements accurately in broiler diets (Stilborn et al 2010;Abd El-Moneim et al 2019;Saleh et al 2019b).…”
Section: Discussionmentioning
confidence: 99%